Genome-wide DNA methylation analysis of pseudohypoparathyroidism patients with GNAS imprinting defects. Issue 1 (December 2016) - Rochtus, Anne; Martin-Trujillo, Alejandro; Izzi, Benedetta; Elli, Francesca; Garin, Intza; Linglart, Agnes; Mantovani, Giovanna; Perez de Nanclares, Guiomar; Thiele, Suzanne; Decallonne, Brigitte; Van Geet, Chris; Monk, David; et al.
Abstract Background Pseudohypoparathyroidism (PHP) is caused by (epi)genetic defects in the imprintedGNAS cluster. Current classification of PHP patients is hampered by clinical and molecular diagnostic overlaps. The European Consortium for the study of PHP designed a genome-wide methylation study to improve molecular diagnosis. Methods The HumanMethylation 450K BeadChip was used to analyze genome-wide methylation in 24 PHP patients with parathyroid hormone resistance and 20 age- and gender-matched controls. Patients were previously diagnosed withGNAS -specific differentially methylated regions (DMRs) and include 6 patients with knownSTX16 deletion (PHPΔstx16 ) and 18 without deletion (PHPneg ). Results The array demonstrated that PHP patients do not show DNA methylation differences at the whole-genome level. Unsupervised clustering ofGNAS -specific DMRs divides PHPΔstx16 versus PHPneg patients. Interestingly, in contrast to the notion that all PHP patients share methylation defects in theA/B DMR while only PHPΔstx16 patients have normalNESP, GNAS-AS1 andXL methylation, we found a novel DMR (namedGNAS-AS2 ) in theGNAS-AS1 region that is significantly different in both PHPΔstx16 and PHPneg, as validated by Sequenom EpiTYPER in a larger PHP cohort. The analysis of 58 DMRs revealed that 8/18 PHPneg and 1/6 PHPΔstx16 patients have multi-locus methylation defects. Validation was performed forFANCC andSVOPL DMRs. Conclusions This is the first genome-wide methylation study for PHP patients that confirmed thatGNAS is the most significant DMR, and the presence ofSTX16 deletion divides PHP patients in two groups. Moreover, a novelGNAS-AS2 DMR affects all PHP patients, and PHP patients seem sensitive to multi-locus methylation defects.